Pullout Strength of Pedicle Screws Following Redirection After Lateral or Medial Wall Breach. Issue 17 (1st September 2018) - Maeda, Toru; Higashino, Kosaku; Manabe, Hiroaki; Yamashita, Kazuta; Hayashi, Fumio; Goda, Yuichiro; Tsuruo, Yoshihiro; Sairyo, Koichi
Abstract : Study Design: A cadaveric biomechanical study designed to test the pullout strength of pedicle screws. Objective: To evaluate the pullout strength of redirected pedicle screws with a larger diameter following lateral wall breach, redirected pedicle screws of the same diameter following medial wall breach, and redirected pedicle screws with a larger diameter following medial wall breach. Summary of Background Data: Screw malposition is one of the main pitfalls of inserting pedicle screws. Intraoperatively a malpositioned screw is redirected and inserted along the correct axis. Methods: Forty-seven vertebrae (T9-L5) were harvested from eight fresh cadaveric spines. The 18 pedicle screws that breached the lateral wall were then removed and redirected using a pedicle screw of 1 mm larger in diameter. The 16 pedicle screws that had breached the medial wall were then removed and redirected using a pedicle screw of the same diameter. The other 13 pedicle screws that had breached the medial wall were then removed and redirected using a pedicle screw of 1 mm larger in diameter. The pullout strength was measured. Results: Following lateral wall breach, mean pullout strength for the larger redirected screws was 46.9% greater than that of the correctly aligned screws. Following medial wall breach, mean pullout strength for the redirected screws of the same diameter was 20.6% less than that of the correctly aligned screws. Mean pullout strength for the larger pedicle screws following medial wall breach was 27.3% more than that of the correctly aligned screws. Conclusion: Redirected pedicle screws of larger diameter after a lateral or medial pedicle breach show recovery of pullout strength. However, the pullout strength of redirected pedicle screws of the same diameter after a medial pedicle breach is significantly less than that of correctly aligned screws. Level of Evidence: 1